Comparisons of Clinical Outcomes and Prognoses in Patients With Gastroesophageal Junction Adenocarcinoma, by Transthoracic and Transabdominal Hiatal Approaches: A Teaching Hospital Retrospective Cohort Study. Issue 50 (December 2015) - Zhou, Jinzhe; Wang, Hao; Niu, Zhaojian; Chen, Dong; Wang, Dongsheng; Lv, Liang; Li, Yu; Zhang, Jian; Cao, Shougen; Shen, Yi; Zhou, Yanbing
Abstract : Abstract: To compare the clinical outcomes and prognoses in patients with gastroesophageal junction adenocarcinoma (Siewert type II/III), by transthoracic and transabdominal hiatal approaches. Siewert II/III gastroesophageal junction adenocarcinomas patients (334 cases) underwent different surgical procedures at the Affiliated Hospital of Qingdao University from July 2007 to July 2012 and were analyzed retrospectively. In total, 140 patients underwent surgery by the transthoracic approach, and 194 patients underwent the transabdominal hiatal approach mainly with radical total and proximal gastrectomy (D2). All patients were followed up by telephone review or by outpatient reexamination until July 2013. The surgically related and clinical outcomes were compared using the χ 2 test, t test, Fisher exact test, or nonparametric rank sum test according to different data. The survival curve was drawn by the Kaplan–Meier method and survival analysis used Cox regression analysis. The operative time, length of resected esophagus, number of lymph nodes harvested, postoperative pain scores, postoperative hospital stay, time of antibiotics use, postoperative morbidity, and costs for the transabdominal surgery group were better than that of the transthoracic group. The overall 5-year survival rate was 35.3% and 40.3%, respectively, in the transthoracic and transabdominal surgery groups, and differences were not statistically significant (x 2 = 2.311, P > 0.05). The hazard ratio of death for the transthoracic compared with the transabdominal approach was 1.27 (0.93–1.72, P > 0.05). According to tumor node metastasis (TNM) staging, stratification analysis showed that stage III patient overall survival rates were 25.7% and 37.2%, respectively. The differences were statistically significant (x 2 = 4.127, P < 0.05). In uni- and multivariate Cox regression analysis, the hazard ratio for the transabdominal versus the transthoracic approach was 0.66 (0 43 to 0.99, P < 0.05) and 1.47 (1.05–2.06, P < 0.05), respectively. There were no significant differences of 5-year overall survival in TNM stage I and II of the Siewert II/III adenocarcinoma patients, but improved survival of TNM stage III patients undergoing transabdominal hiatal compared with transthoracic total radical and proximal gastrectomy. The short-term clinical outcomes improved with the transabdominal hiatial surgery group.